Intersection management strategies to realise the benefits of new generation vehicles - Wu, Yuanyuan (Nanyang Technological University, 2021)
Automation and wireless communication technologies are bringing us the new-generation vehicles: Connected and Automated Vehicles (CAVs). This thesis aims to investigate the impacts and leverage of the advanced features of CAVs on traffic flow at road junctions, and propose corresponding intersection management to realise the promising benefits of CAVs.